PVA-CoFe2O4-Biochar Composites: Structure and Properties - Frolova, Liliya A.; Saltykov, Dmytro Yu.; Kushnerov, Oleksandr I.; Olkhov, Kostyantin V.; Nikitin, Maksim O.; Rodin, Dmytro O. (Oles Honchar Dnipro National University, Dnipro, 2025)
ENG: PVA-CoFe2O4-biochar composites were synthesized by a two-stage combined method. The resulting composites were characterized by X-ray diffraction, scanning electron microscopy, UV-visible absorption spectroscopy, vibrational magnetometry, and vector microwave analysis. The results of electron microscopy show that biochar has a block structure with large pores, so this structure can be used in the creation of composites. The magnetic properties depend on the content of cobalt ferrite in the composite. The results of the study of photocatalytic properties showed that the rate of destruction of methylene blue (MB) is 50–98% after 60 min of UV radiation. It was established that the reaction of photocatalytic decomposition of MB obeys pseudo-first-order kinetics. Among these catalysts, biochar showed the highest rate constant of 0.085 min−1, PVA/CoFe2O4-biochar composites – 0.05 min−1. When studying the absorption of electromagnetic radiation in the radar range from 8 GHz to 12 GHz by PVA/CoFe 2O4- biochar composites, it was found that with an increase in the ratio of CoFe2O4-bichar components to 0.67 wt. parts CoFe2O4, the absorption losses of the composite reach –14.15 dB/mm at a frequency of 8 GHz and –12.37 dB at a frequency of 12 GHz.

UKR: Композити ПВС-CoFe2O4-біовугілля синтезовані двостадійним комбінованим методом. Отримані композити були охарактеризовані методами рентгенівської дифракції, скануючої електронної мікроскопії, спектроскопії поглинання в УФ-видимій області, вібраційної магнітометрії та векторного мікрохвильового аналізу. Результати електронної мікроскопії показують, що біовугілля має блокову структуру з великими порами, тому ця структура може бути використана у створенні композитів. Магнітні властивості залежать від вмісту фериту кобальту в композиті. Результати дослідження фотокаталітичних властивостей показали, що швидкість деструкції метиленового синього (МС) становить 50–98 % після 60 хв дії УФ-випромінювання. Встановлено, що реакція фотокаталітичного розкладу MB підпорядковується кінетиці псевдопершого порядку. Серед цих каталізаторів біовугілля показало найвищу константу швидкості 0,085 хв−1, композити PVA/CoFe2O4-біовугілля – 0,05 хв−1. Під час вивчення поглинання електромагнітного випромінювання в радіолокаційному діапазоні від 8 ГГц до 12 ГГц композитами PVA/CoFe2O4- біовугілля встановлено, що зі збільшенням співвідношення компонентів CoFe2O4-бівугілля до 0.67 мас.ч. CoFe2O4 втрати поглинання композиту сягають –14.15 дБ/мм на частоті 8 ГГц і –12.37 дБ на частоті 12 ГГц.
Композити PVA-CoFe2O4-Біочар: структура та властивості
Liliya A. Frolova: ORCID 0000-0001-7970-2264; Oleksandr I. Kushnerov: ORCID 0000-0002-9683-2041; Dmytro O. Rodin: ORCID 0009-0004-6902-5473
Keywords: magnetic properties; spinel; X-ray phase analysis; магнітні властивості; шпінель; рентгенофазовий аналіз; КТНРтаЕ; TECHNOLOGY; NATURAL SCIENCES; Chemistry